The Effect Of Performance Allowances On Motivation, Employees' Work Achievement and Organizational Performance in Government Offices - Muhammad Mudhofar (Universitas Medan Area, 2021)
This study aims to analyze the effect of performance allowance as a determinant of motivation, employees’ work achievement and organizational performance in the Ministry of Religion's Office Lumajang City. This determining variable is important for public organizations to improve services and fulfill bureaucratic reform. This quantitative research uses Structural Equation Modeling (SEM) data analysis tools with AMOS software. The research population was 153 Ministry of Religion employees. The modeling results show the GFI index value of 0.906; CFI 0.969; and RMSEA 0.040. Hypothesis testing shows the insignificant direct effect between performance allowance and motivation, employees’ work achievement and organizational performance. Factors that determine the improvement in performance of public organizations are directly and significantly affected by by work achievement. Work achievement contributes the most to organizational performance. High work achievement requires a number of supporting factors, namely performance allowance and motivation. This research provides a practical contribution in policy making for government organizations regarding efforts to improve organizational performance through work achievement. Performance allowance and motivation is an important element to directly improve employee work achievement as a medium to improve organizational performance. The originality value of this research is very good because it was first carried out on the object of a public organization that has just applied compensation payments for the State Civil Apparatus in the form of performance allowances by testing and measuring the implications of the compensation factor as a determinant of organizational performance.